Biologia versus kultura. Przegląd bioewolucyjnych i kulturowych teorii wojny w przedpaństwowych społecznościach pradziejowych - Skrzyniecki, Rafał; Romaniszyn, Jan (Folia Praehistorica Posnaniensia, 2016)
The paper’s main aim is to outline the problem of polarisation of contemporary discussion concerning the concept of origins of warfare. Basically, two leading trends can be distinguished: the first one accentuates the biological basis of human violence and places its origins deep into our evolutionary past. The second one recognises conflict as a relatively late and typically cultural phenomenon in human prehistory, which cannot be interpreted in terms of natural selection and evolution. The existence of a sharp ideological border between ‘hawks’ and ‘doves’ enables a comparison of both perspectives and facilitates the analysis of internal dynamics of their development.